Treatment preferences of patients with chronic low back pain in physical therapy clinics in Saudi Arabia: a cross-sectional study - Maryam Alasfour; Majd Bajnaid; Salhah Hobani; Muhammad Alrwaily (PeerJ)
Background Low back pain (LBP) is a prevalent musculoskeletal disorder that significantly contributes to disability and health care burden. Clinical practice guidelines (CPGs) recommend non-pharmacological interventions, such as those delivered by physical therapists, to improve clinical outcomes. Incorporating patient preferences into treatment decisions is essential for promoting patient-centered care and enhancing adherence to CPGs. This study aimed to explore the physical therapy treatment preferences of patients with chronic LBP (CLBP) in Saudi Arabia and to evaluate their alignment with CPG recommendations. Methods This cross-sectional survey-based study was conducted across three healthcare centers in Saudi Arabia. Patient preferences were assessed using a validated questionnaire that listed available physical therapy treatments for CLBP. The participants were provided with a standardized explanation of evidence-based treatment options based on the updated CPGs for LBP before selecting their preferred treatments. Data analysis included descriptive statistics and chi-square tests to assess the alignment of preferences with CPG recommendations. Results A total of 138 participants were included, with 60.1% of the selected treatments aligning with CPG recommendations (p < 0.001). Sociodemographic factors, such as sex, prior physical therapy experience, and body mass index (BMI), influenced treatment preferences. Exercise was the most preferred treatment, aligning with CPGs, while passive modalities, such as interferential therapy, were also frequently chosen despite not being recommended. Conclusion This study highlights the importance of understanding patient preferences to improve adherence to CPGs and promote evidence-based care for CLBP. Educational interventions tailored to the cultural context can bridge the gap between patient preferences and evidence-based recommendations, empower patients, and enhance clinical outcomes.